ENTREPRENEURIAL POTENTIAL OF FORESTRY UNDER MARTIAL LAW - Tarasiuk, Iryna (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
The features of the transformation of the entrepreneurial potential of forestry enterprises in Ukraine under martial law are considered. It is proven that the industry, which traditionally combines economic, environmental and social functions, is simultaneously subject to the destructive influence of external factors and stimulating effects that open up new directions of development. Changes in the financial, labor, technical, innovative and managerial components of the potential are identified. In the process of the study, internal and external factors of influence on the entrepreneurial activity of forestry enterprises were analyzed. Based on the analysis, the following strategic guidelines for the restoration and development of potential are proposed: digitalization of management, formation of cluster associations, strengthening of innovative activity and implementation of educational programs for personnel training. It was determined that support from the state and international partners is important for the stable development of the industry and ensuring its contribution to the restoration of the national economy after the end of the war.